Planeación financiera a la empresa comercial “Acabados del Austro” de la ciudad de Loja, periodo 2023-2027. - Cuenca Cuenca, Geovanny Gabriel (2023)
The Curricular Integration work called: Financial planning for the commercial company "Acabados del Austro" in the city of Loja, period 2023-2027, was developed with the purpose of implementing the use of a financial tool according to the activities and economic operations that the entity performs daily, this will provide a significant contribution to the administrative staff and thus the owner so they can optimize the available resources and achieve increased profitability in the coming years and also will be a relevant tool for financial decision making. In order to comply with the specific objectives, we began with the collection of information and financial statements for the periods 2020 and 2021 of the commercial enterprise, we started with the development and application of financial indicators, since their function is of vital importance to measure the economic, operational and financial performance of the economic unit. Likewise, in order to execute the second specific objective, a sales and purchases forecast was developed, with the purpose of knowing future economic results, which allows making the most of the opportunities, using as base information the historical sales and purchases of the year 2021 and applying an accounting policy within the company, The projections were made by applying the percentage increase method, allowing to know the growth that existed between these two periods, since, thanks to the forecasts, it was possible to know the acquisition needs, the increases and decreases that will be obtained in the company. The main function of the Cash Budget is to forecast future cash inflows and outflows, and to prevent future situations. In order to fulfill the last specific objective, we proceeded to the preparation of the Income Statement and the Proforma Statement of Financial Position, in order to know the expected income, costs and expenses for the years 2023-2027. The methodology used for the curricular integration work is documentary research because it focuses on a bibliographic review of books, magazines, documents, websites, articles, among others, which allowed us to obtain the most relevant aspects of collecting and selecting the information starting with the financial statements which allowed us to perform financial planning in the economic unit. Finally, the conclusions and recommendations are described, which are written based on the results obtained. It is concluded that the commercial company Acabados del Austro does not have financial planning, financial policies (purchases and sales), purchase and sales forecasts and cash budget, which is why it does not know the current and future financial situation, in order to take corrective measures to increase economic and financial profitability.